Meningkatkan Kemampuan Motorik Halus Melalui Bermain Playdough - Ika Pribianti; Yurna Devi; sri Rejeki (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The background to this research is the low fine motor skills of children which can be seen from the children still having difficulty in imitating making lines, children still having difficulty in cutting activities where the results of the cutting do not match the pattern and the children still being weak in eye and hand coordination. Therefore, efforts are needed to improve children's fine motor skills through playdough activities.The aim of this research was to determine the fine motor skills of children aged 5-6 years at the Tunas Harapan Pagaran Tapah Kindergarten, Rokan Hulu Regency. The benefit of this research is that it is hoped that it will be useful as knowledge to improve children's fine motor skills through playing with playdough. This type of research is classroom action research which is carried out in 2 cycles, each cycle being carried out in 3 meetings. The classroom action research design consists of 4 activities in 1 cycle, namely planning, action, observation and reflection. The data collection tool used in this research is an observation sheet. The subjects in this research were 15 children from group B at Tunas Harapan Kindergarten, consisting of 9 boys and 8 girls. Based on the analysis of the assessment process from 2 cycles there was an increase, the increase that occurred was from pre-cycle to cycle I of 28.25%, cycle I to cycle II of 45.29% and an increase from pre-cycle to cycle II of 86.34%. From the results of this research, it was concluded that playing with playdough can improve children's fine motor skills in children aged 5-6 years at Tunas Harapan Pagaran Tapah Kindergarten, Rokan Hulu Regency. Keywords: Fine motor skills, playdough, playing